БИР МӘРТЕЛИК ПАРОЛЬ ТИЙКАРЫНДА БИР БАҒДАРЛЫ АУТЕНТИФИКАЦИЯ ПРОТОКОЛЛАРЫНЫҢ АНАЛИЗИ - Арзиева, Ж.Т.; Калмуратова, С.М. (SCIENCE and SOCIETY, 2021)
The article deals with the state presented the analysis of protocols of single authentication on the basis of single passwords. A comparative analysis is presented OTP transmission methods in autnentification methods based on one-time passwords.
Keywords: one-time password; OTP; HOTP algorithm; TOTP algorithm; SMS; smart card; token; RSA Security